2015
DOI: 10.1159/000438870
|View full text |Cite|
|
Sign up to set email alerts
|

Minor Elevation in C-Reactive Protein Levels Predicts Incidence of Erythropoiesis-Stimulating Agent Hyporesponsiveness among Hemodialysis Patients

Abstract: Background: Hemodialysis (HD) patients occasionally experience minor asymptomatic elevation in C-reactive protein (CRP) levels, which may be associated with difficulty in managing renal anemia using erythropoiesis-stimulating agents (ESAs). Here, we assessed whether elevation of CRP predicts future incidences of ESA hyporesponsiveness. Methods: A total of 2,956 HD patients lacking ESA hyporesponsiveness and infectious diseases were enrolled, and the association between CRP levels and incidence of ESA hyporespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
(65 reference statements)
1
26
0
Order By: Relevance
“…A disturbance in the crosstalk between inflammation, iron metabolism and erythropoiesis may, therefore, favor ESA hyporesponsiveness. The best predictors for ESA response appear to be IL-6 and CRP [88,89]. Studies conducted by our group showed that HD patients with poorer response to ESA present higher levels of pro-inflammatory cytokines [90,91]; moreover, in studies using a rat model of chronic renal failure, we found that the severity of the inflammatory state was related to the reduction in the rHuEPO response [92].…”
Section: Hypoxia and Human Diseasesmentioning
confidence: 66%
“…A disturbance in the crosstalk between inflammation, iron metabolism and erythropoiesis may, therefore, favor ESA hyporesponsiveness. The best predictors for ESA response appear to be IL-6 and CRP [88,89]. Studies conducted by our group showed that HD patients with poorer response to ESA present higher levels of pro-inflammatory cytokines [90,91]; moreover, in studies using a rat model of chronic renal failure, we found that the severity of the inflammatory state was related to the reduction in the rHuEPO response [92].…”
Section: Hypoxia and Human Diseasesmentioning
confidence: 66%
“…Chronic inflammation produces cytokines, thus inhibiting erythropoiesis and shortening the lifespan of red blood cells [19, 20]. In patients with secondary hyperparathyroidism, parathyroid hormone can reduce the synthesis of endogenous EPO, inhibit the maturation of erythrocyte precursors, and shorten the erythrocyte lifespan by increasing the osmotic fragility of erythrocytes [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…While BMI is indeed an imperfect measure of adiposity compared with other metrics of obesity [36-38], this index remains the most easily applicable measure of body build in routine assessments in daily clinical practice and provides valuable information on the global nutritional status, including both muscle and fat mass [39]. Second, our study included only Japanese HD patients who tend to be older and have longer dialysis vintage than those in other countries [40, 41]; as such, the results may not be generalizable to patients from other geographical areas. However, given the aging of the worldwide HD population and consequent improvements in the outcomes in HD patients, we feel it reasonable to expect decent external validity of our findings, at least in other countries or regions where the clinical outcomes of HD patients are better or comparable to those in Japan.…”
Section: Discussionmentioning
confidence: 99%